2016
DOI: 10.1002/jmri.25280
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial strain in healthy adults across a broad age range as revealed by cardiac magnetic resonance imaging at 1.5 and 3.0T: Associations of myocardial strain with myocardial region, age, and sex

Abstract: PurposeTo assess myocardial strain using cine displacement encoding with stimulated echoes (DENSE) using 1.5T and 3.0T MRI in healthy adults.Materials and MethodsHealthy adults without any history of cardiovascular disease underwent magnetic resonance imaging (MRI) at 1.5T and 3.0T within 2 days. The MRI protocol included balanced steady‐state free‐precession (b‐SSFP), 2D cine‐echo planar imaging (EPI)‐DENSE, and late gadolinium enhancement in subjects >45 years. Acquisitions were divided into six segments; gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
3
19
1
1
Order By: Relevance
“…Deformation-tracking identified a sex difference in strain as previously reported using DENSE25, i.e. that females may generate larger magnitudes of circumferential strain.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Deformation-tracking identified a sex difference in strain as previously reported using DENSE25, i.e. that females may generate larger magnitudes of circumferential strain.…”
Section: Discussionsupporting
confidence: 58%
“…Image analysis is as previously described25. The imaging datasets were anonymised to ensure that the imaging analysts were blinded to all other data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CMR data were analysed from 65 patients diagnosed with SSc, whereof 40 without PAH and 25 with PAH. Nineteen healthy controls, from earlier studies in our group (Steding et al, 2010;Bodetoft et al, 2011;Gyllenhammar et al, 2018), were matched with the patient population for gender and age (Mangion et al, 2016). Controls had no reported morbidities, including arterial hypertension, diabetes or coronary artery disease, no medical history or medication, and were checked by clinicians before entering the study.…”
Section: Study Populationmentioning
confidence: 99%
“…Mangion et al showed that global cine‐strain measurements offer good reproducibility, whereas regional strain is less reproducible . Additionally, myocardial strain parameters are associated with age and sex, which suggests analysis of strain should account for these differences . Figures show circumferential and radial strain calculations with both global and segmental approaches utilizing feature tracking.…”
Section: Cancer Therapeutics‐related Cardiac Dysfunctionmentioning
confidence: 99%